Understanding volunteerism: the role of the participant in non-clinical correctional programming. Issue 7 (3rd October 2022) - Butler, H. Daniel; Campagna, Michael F.; Spohn, Ryan; Towne, Katelynn
Abstract: Most incarcerated individuals do not participate in prison programming, which may be due to the limited availability of programs or the voluntaristic nature of programming. Most incarcerated individuals are provided the opportunity to select their own non-clinical programming. This voluntaristic approach to program participation provides an opportunity to explore the characteristics of who opts into non-clinical programming when given the choice, an inquiry that acknowledges potential practical and ethical limitations to a non-clinical delivery of programming. In this study, we utilize administrative data from a Midwestern state to understand who volunteers for correctional programming in institutional and community settings. Findings reveal days incarcerated and gender are the strongest predictors of volunteerism for a broad array of correctional programs. Implications include a deeper understanding of volunteer characteristics that may assist agencies to adjust strategies aimed at improving correctional outcomes.